The Effect of Addition of Ash from Burning Wood Powder to the Mechanical and Physical Properties of Concrete - yusnitaerna erna (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
The wood powder is the waste from woods industry that further used as a mixture of plant soil. Scientist have used the powder of wood to make a particle board. This research, We used the ash of wood powder as an additive thing in the concrete mixture. The test is done for physics and mechanics of the concrete. The sample is made from the ingredients 1 cement : 2 sand : 3 pebble. In variation add to ash of the wood powder for cement is 5%, 10%, and 15%. The result of the researching show that the used of the ash of wood powder can build the impact of the concrete is 9.54% from normal concrete with the mixture of the ash of wood powder is 15%. Orther side for the physics, the water absorption and porosity with the ash of the wood powder is from 4.94% to 14.35% and from 4.16% to 14.89% higher than the normal concrete.